2013
DOI: 10.2480/agrmet.69.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental lighting to a lower leaf using light-emitting diodes with different spectra on the leaf photosynthetic rate in sweet pepper

Abstract: Intracanopy lighting (IL) is a newly proposed supplemental lighting technique, irradiating lower leaves of plants from light sources placed between plant stands in high-wire grown vegetable production in a greenhouse. Light-emitting diodes (LEDs) are an appropriate light source for IL because of their compactness and low operating temperatures. To take advantage of features of LEDs, which emit light with a narrow band of wavelengths, we investigated short-term effects of spectra on instantaneous photosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…the responses of P n to changes in PFD and/or C i ). Several studies have reported that the SPD of the ML affected the P n of leaves (McCree , Inada , Hogewoning et al , Murakami et al ). To eliminate this direct effect, measurements of photosynthetic parameters should be made under identical SPD conditions, irrespective of the SPD of GL.…”
Section: Discussionmentioning
confidence: 99%
“…the responses of P n to changes in PFD and/or C i ). Several studies have reported that the SPD of the ML affected the P n of leaves (McCree , Inada , Hogewoning et al , Murakami et al ). To eliminate this direct effect, measurements of photosynthetic parameters should be made under identical SPD conditions, irrespective of the SPD of GL.…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuating light and shade-flecks due to shading from the upper canopy have been associated with reduced growth (Kaiser et al 2018;; however, the addition of intracanopy lighting can improve light distribution throughout the canopy (Frantz et al 2000;Pettersen et al 2010), increasing photosynthesis in lower leaves that would otherwise present a significant metabolic burden for the plant (Frantz et al 2000). It should be noted that any increases in photosynthesis by intracanopy lighting remain sensitive to the choice of light spectrum (Murakami et al 2013), and fine-tuning of light spectra may affect rates of photosynthesis more than morphology and fruit yield (G omez and Mitchell 2016b). Although intracanopy lighting is another tool for light spectrum-based manipulation of plant morphology and performance, we note that evidence of impact remains ambiguous.…”
Section: Supplementary and Intracanopy Lightingmentioning
confidence: 99%
“…Light has an impact on plant physiology, flowering, secondary metabolite accumulation, nutrient transport and plant quality [14][15][16][17][18][19]. Different light spectra can influence the processes of plant part growth.…”
Section: Introductionmentioning
confidence: 99%